A Toolbox of Ideas for the Geoscientist Working on Block Cave Mines - N Burgio (The Australasian Institute of Mining and Metallurgy, 2011)
Block cave mines are often thought of as rock factories where high volumes of production are mined from a fixed area suggesting little requirement for geological input and control. Yet caving operations have peculiar and specific technical requirements from prefeasibility through to post-mining reconciliation. Whilst essential elements such as resource definition, geological interpretation and sampling strategies are common to all mining methods, planning for a block cave requires a different emphasis and philosophical approach in how we deal with these issues. We will examine why a geoscientist’s input is critical towards the successful planning, design and monitoring of a caving operation.